Primary Ewing's Sarcoma of the temporal bone in an infant - Goudarzipour, Kourosh; Shamsian, Shahin; Alavi, Samin; Nourbakhsh, Kazem; Aghakhani, Roxana; Eydian, Zahra; Arzanian, Mohammad Taghi (International journal of hematology- oncology and stem cell research, 2015)
Introduction : Ewing's sarcoma is the second most common primary malignant tumor of bone found in children after Osteosarcoma. It accounts for 4-9% of primary malignant bone tumors and it affects bones of the skull or face in only 1-4% of cases. Hence it rarely affects the head and neck. Subject and Method : In this case report, we describe a case of primary Ewing's sarcoma occurring in the temporal bone. The tumor was surgically excised, and the patient underwent chemotherapy for ten months. Results : Neither recurrence nor distant metastasis was noted in these 10 months after surgery but about 18 months after surgery our patient was expired. Conclusion : Although the prognosis of Ewing's sarcoma is generally poor because of early metastasis to the lungs and to other bones, a review of the article suggested that Ewing's sarcoma occurring in the skull can often be successfully managed by intensive therapy with radical excision and chemotherapy. This result was supported by the case reported here.